(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The purpose of this study was to investigate the relationship between wicking coefficients of fabrics and yarns. A range of plain fabrics were woven by varying the weave density, yarn count and fibre content. From experiments on the in-plane capillary water flow within these fabrics and the yarns obtained from the corresponding fabric, the wicking coefficients of fabrics and yarns were determined. The wicking coefficient was higher for lower weave density because of the effective capillary radius. The results for four kinds of yarns showed that the 100% cotton yarn and cotton fabric had the highest wicking rate. Based on scanning electron microscope observation of cross section and longitudinal section of yarns, we discussed the effects of inter-fibre space and yarn twist on the wicking influence factor and found that the wicking rate is higher for larger inter-fibre space and yarns with fewer twists.